2020
DOI: 10.1038/s41467-020-14646-w
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-genomic landscape of osteosarcoma

Abstract: Limited clinical activity has been seen in osteosarcoma (OS) patients treated with immune checkpoint inhibitors (ICI). To gain insights into the immunogenic potential of these tumors, we conducted whole genome, RNA, and T-cell receptor sequencing, immunohistochemistry and reverse phase protein array profiling (RPPA) on OS specimens from 48 pediatric and adult patients with primary, relapsed, and metastatic OS. Median immune infiltrate level was lower than in other tumor types where ICI are effective, with conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
169
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(179 citation statements)
references
References 60 publications
8
169
2
Order By: Relevance
“…The PD-L1-positive samples also exhibited a higher level of immune cell infiltration than their PD-L1-negative counterparts [47]. This is in line with the finding that osteosarcomas with high levels of immune infiltration are enriched in immune downregulation pathways, including PD-1 signalling and the CTLA-4 pathway [52]. Collectively, this suggests that osteosarcoma may utilize PD-L1, PD-L2, B7-H3, and CTLA-4 to counteract immune recognition.…”
Section: The Tumour Microenvironmentsupporting
confidence: 85%
See 1 more Smart Citation
“…The PD-L1-positive samples also exhibited a higher level of immune cell infiltration than their PD-L1-negative counterparts [47]. This is in line with the finding that osteosarcomas with high levels of immune infiltration are enriched in immune downregulation pathways, including PD-1 signalling and the CTLA-4 pathway [52]. Collectively, this suggests that osteosarcoma may utilize PD-L1, PD-L2, B7-H3, and CTLA-4 to counteract immune recognition.…”
Section: The Tumour Microenvironmentsupporting
confidence: 85%
“…A summary of therapeutic targets that have led to clinical trials in osteosarcoma is presented in Table 1. [197,198,200] Pooled IFNα added to standard treatment yielded better outcome in a nonrandomized trial [194] IFN-α-2b together with MAP did not improve outcome in a large randomized trial [130] Inhalation of aerosolized GM-CSF did not hinder disease progression nor improve outcome [199] L-MTP-PE showed some effects on survival (but interactions with ifosfamide in a factorial study design) [116,201] CTLA-4 Negative regulator of cytotoxic T-cells Osteosarcomas are enriched in CTLA-4 pathways [52] Ipilimumab showed partial responses or stable disease in a small number of paediatric patients [204] PD-1 Negative regulator of cytotoxic T-cells Patients positive for PD-1 ligand had worse event-free survival, and osteosarcomas are enriched in PD-1 signalling [52] Nivolumab showed some efficacy in adults [205] Pembrolizumab had limited efficacy in adults [206] ErbB/Her receptors (including Her1, Her2, Her3, Her4, and EGFR)…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…In addition to analyzing the influence of CD4 and CD68, we also explored other potential prognostic immune genes. Similarly, naive CD8+ T cells can respond to tumor antigens and differentiate into cytotoxic effector cells, while γδT cells have the property of killing tumor cells (39,40). Our analysis revealed that although naive CD8+ and γδT cells were significantly related to prognosis, they exhibited low abundance in OSA; hence, we did not carry out further in-depth analysis of these cells.…”
Section: Discussionmentioning
confidence: 84%
“…Samples with low immune infiltration had a higher number of deleted genes including MHC, while those with high immune infiltration expressed higher levels of adaptive resistance pathways. They concluded that these multi-resistant pathways inhibit the effect of immunotherapy for osteosarcoma ( Figure 5 [ 90 ]).…”
Section: Challenges For the Futurementioning
confidence: 99%